Livestock database management: preliminary studies in Malaysia / F. Saad, R. Ismail and I. Ismail - Saad, F.; Ismail, R.; Ismail, I. (UiTM Press, 2016)
This paper outlined the preliminary studies in Malaysia for livestock database management. Livestock area signifies the biggest food industry segment in Malaysia. Selfsufficiency in livestock product for beef, mutton and dairy product is claimed to be low by the Department of Veterinary Services (DVS) in year 2015, which is less than 30%. To improve the current Malaysia livestock industry, this paper proposes a better management system especially in handling database of the cattle at Malaysian Agricultural Research and Development Institute (MARDI). The objectives of this work are; to study and propose on livestock database management system architecture and to develop graphical user interface (GUI) for livestock management system. A system combining the RFID technology supported with GUI is developed using VisualBasic.NET for four sections that are breeding, feedlot-fattening, dairying and slaughtering. User may update the data on the GUI and view existing data collected from the tag, which is then automatically updated at the central database. The data gathered on temperature will be further analyzed for early detection of disease.